2022
DOI: 10.3389/fonc.2022.929949
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo range verification analysis with in-beam PET data for patients treated with proton therapy at CNAO

Abstract: Morphological changes that may arise through a treatment course are probably one of the most significant sources of range uncertainty in proton therapy. Non-invasive in-vivo treatment monitoring is useful to increase treatment quality. The INSIDE in-beam Positron Emission Tomography (PET) scanner performs in-vivo range monitoring in proton and carbon therapy treatments at the National Center of Oncological Hadrontherapy (CNAO). It is currently in a clinical trial (ID: NCT03662373) and has acquired in-beam PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…On the other hand, it is be somewhat less sensitive to fluctuations in the values in distal activity, since it does not look at a threshold value, but tries to find the best matching δR value for the end-of-range profile. This method is being tested on data, as reported in [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is be somewhat less sensitive to fluctuations in the values in distal activity, since it does not look at a threshold value, but tries to find the best matching δR value for the end-of-range profile. This method is being tested on data, as reported in [21].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment plan for each patient was simulated, additionally with the last part of the CNAO beam line, including the exit window and nozzle (Molinelli et al 2013, Magro et al 2015, Mirandola et al 2015, the patient geometry (from the CT scan to a voxel FLUKA geometry), radiation transport and interactions of protons in the patient. These data are then used to reconstruct the AMs in a field of view of 140 × 70 × 165 and with a resolution of 1.6 mm × 1.6 mm × 1.6 mm (Fiorina et al 2021, Kraan et al 2022, Moglioni et al 2022, as displayed in figure 2.…”
Section: Patient Datamentioning
confidence: 99%
“…A small cohort of them (clinical trial registered under ID: NCT03662373) has been monitored with the INSIDE IB-PET scanner (Bisogni et al 2016, Bisogni 2019. Recent studies based both on MC simulation and the acquired INSIDE IB-PET data have shown the possibility of detecting morphological changes using range variation or 3D methods (Fiorina et al 2021, Kraan et al 2022, Moglioni et al 2022, Moglioni et al 2023. To the best of our knowledge, these are the most recent papers regarding attempts to correctly locate and identify the morphological change in patients starting from PET data.…”
Section: Introductionmentioning
confidence: 99%
“…PET provides 3D information about the activity distribution based on the produced radioisotopes during the PT 10 . Several studies have demonstrated the feasibility of range verification, dose quantification, and inter‐fractional morphological changes of patient using the PET system 3,11 . However, PET imaging suffers from certain limitations such as delayed signal emission and wash out effects which reduce its spatial resolution, thereby limiting its applicability for the online imaging of the single spots 12 .…”
Section: Introductionmentioning
confidence: 99%